THE RELATIONSHIP BETWEEN SANITARY HYGIENE AND THE PRESENCE OF ESCHERICHIA COLI IN ICED SUGARCANE JUICE SOLD IN TEBING TINGGI CITY - Safira, Putri; Ashar, Yulia Khairina; Nanda, Meutia; Wahyudi, Wahyudi (Pusat Studi Gender dan Anak, 2025)
Iced sugarcane juice that contains coliform bacteria indicates the presence of microbiological contamination. Contamination by pathogenic bacteria such as Escherichia coli can lead to various health problems, including gastrointestinal infections, diarrhea, and other diseases. This study aims to analyze the relationship between hygiene and sanitation practices and the presence of Escherichia coli in iced sugarcane juice sold in Tebing Tinggi City. This research is a quantitative study with an observational design using a cross-sectional approach. The population consisted of all iced sugarcane juice vendors in Tebing Tinggi City (57 vendors), with 31 selected as samples through simple random sampling. Laboratory testing was conducted at the Public Health Laboratory Center (BLKM) in Medan. Bivariate analysis showed a significant relationship between hygiene and sanitation variables (p = 0.043; PR = 3.259), food handler hygiene (p = 0.027; PR = 1.943), equipment sanitation (p = 0.032; PR = 1.789), and sanitation facilities (p = 0.045; PR = 1.579) with the presence of Escherichia coli in iced sugarcane juice sold in Tebing Tinggi City. It is expected that iced sugarcane juice vendors implement proper hygiene and sanitation practices to prevent microbiological contamination and protect consumer health.